Critical review of indicators, metrics, methods, and tools for monitoring and evaluation of biofortification programs at scale - Rodas-Moya, Santiago; Giudici, Francesca M.; Mudyahoto, Bho; Birol, Ekin; Kodish, Stephen R.; Lachat, Carl; Abreu, Taymara C.; Melse-Boonstra, Alida; van het Hof, Karin H.; Brouwer, Inge D.; Osendarp, Saskia; Feskens, Edith J. M. (Frontiers in Nutrition, 2022)
Sound monitoring and evaluation (M&E) systems are needed to inform effective biofortification program management and implementation. Despite the existence of M&E frameworks for biofortification programs, the use of indicators, metrics, methods, and tools (IMMT) are currently not harmonized, rendering the tracking of biofortification programs difficult. We aimed to compile IMMT for M&E of existing biofortification programs and recommend a sub-set of high-level indicators (HLI) for a harmonized global M&E framework. We conducted (1) a mapping review to compile IMMT for M&E biofortification programs; (2) semi-structured interviews (SSIs) with biofortification programming experts (and other relevant stakeholders) to contextualize findings from step 1, and (3) compiled a generic biofortification program Theory of Change (ToC) to use it as an analytical framework for selecting the HLI. This study revealed diversity in seed systems and crop value chains across countries and crops, resulting in differences in M&E frameworks. Yet, sufficient commonalities between implementation pathways emerged. A set of 17 HLI for tracking critical results along the biofortification implementation pathway represented in the ToC is recommended for a harmonized global M&E framework. Further research is needed to test, revise, and develop mechanisms to harmonize the M&E framework across programs, institutions, and countries.